PENGARUH KETERLIBATAN KARYAWAN DI DALAM PROSES PELAKSANAAN PEKERJAAN TERHADAP KEEFEKTIFAN ORGANISASIONAL - Dody Hapsoro (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2008)
High involvement management is a term coined by Ed Lawler (1986) for a management approach centered on employee involvement. It entails providing employees with opportunities to make decisions concerning the conduct of their jobs and to participate in the business as a whole. Joblevel involvement means increasing the decision-making opportunities people have in their work, while organizational-level involvement, or empowerment, means giving employees a role in decisions concerned with strategy, investment and other major organizational matters. High involvement management thus involves practices such as team working, empowerment, idea capture schemes, information-sharing on quality, customer feedback and business results, organizational performance-related reward systems, and extensive training and development, including the social and problem-solving skills required for high involvement working. It is conceived as an alternative to a control model based on job simplification, tightly defined divisions of labor, rigid allocations of individuals to narrowly defined tasks and minimal employee participation in higherlevel decisions. The objective of this paper is to explain about two important issues that related with the efforts to build the confidence that high involvement in the process of doing job is an appropriate perspective in explaining about the important meaning of employee involvement for the whole organization. First, the synergy between attributes of high involvement in doing job is presumed will give impact on the organizational effectiveness. Second, to describe various contingent conditions that influences the high involvement in doing job. The previous study that has already done by Riordan, Vandenberg, and Richardson (2005) treat attributes in high involvement in doing job is isolated out of organizational context.